2016
DOI: 10.1371/journal.pone.0145878
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Microbiota in Patients with Spinal Cord Injury

Abstract: Human intestinal flora comprises thousands of bacterial species. Growth and composition of intestinal microbiota is dependent on various parameters, including immune mechanisms, dietary factors and intestinal motility. Patients with spinal cord injury (SCI) frequently display neurogenic bowel dysfunction due to the absence of central nervous system control over the gastrointestinal system. Considering the bowel dysfunction and altered colonic transit time in patients with SCI, we hypothesized the presence of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
140
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(152 citation statements)
references
References 29 publications
5
140
1
6
Order By: Relevance
“…In addition, the small nunber of positive samples in the two groups (12/37) reduced the validity of our results. SCI patients frequently have neurogenic bowel dysfunction, owing to the absence of central nervous system control over the GI system [24]. There are two different bowel dysfunction types in SCI patients: upper motor neuron syndrome and lower motor neuron bowel syndrome [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the small nunber of positive samples in the two groups (12/37) reduced the validity of our results. SCI patients frequently have neurogenic bowel dysfunction, owing to the absence of central nervous system control over the GI system [24]. There are two different bowel dysfunction types in SCI patients: upper motor neuron syndrome and lower motor neuron bowel syndrome [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al reported association between long retention time and decrease of relative abundance of Prevotella [6]. In two other studies, the increase of the transit time resulted in the decreased amounts of Bifidobacterium and Bacteroides [7] or Roseburia, Pseudobutyrivibrio, and Megamonas [8]. …”
Section: Introductionmentioning
confidence: 99%
“…Cani et al [8] demonstrated that lipopolysaccharide, a component of certain gram negative bacterial membranes, can translocation across a "leaky" gut wall, stimulating a cascade of inflammatory cytokine release, increased adiposity, and hyperglycemia. Gungor et al [9] recently described fecal microbiomal shifts among individuals with SCI resulting in reduced production of butyrate, a fatty acid instrumental in preserving gut barrier functions [10]. While our data and the scope of this preliminary work are insufficient to support conclusions about metabolic effects of neurogenic bowel, they raise the possibility of a unifying explanation (microbiomal perturbations with resulting "leaky" gut) for both the adipose deposition in skeletal muscle and the post-prandial hyperglycemia often seen in people with SCI.…”
Section: Discussionmentioning
confidence: 99%